Content-based language teaching with functional grammar in the elementary school. (3rd April 2014) - Schleppegrell, Mary J.
Abstract : Today many second language (L2) teachers work with school-aged learners who need to be supported in their language development at the same time they learn school subjects. Applied linguists and researchers in second language acquisition (SLA) have much to contribute to those teachers, but to do so in more powerful ways calls for an orientation toward the goals of the content classroom. This plenary describes a project in which the theory of systemic functional linguistics is providing useful metalanguage for exploring language and meaning in curricular activities that also support disciplinary learning. It illustrates how language-based content teaching can provide the support children need.